Management of Preventable Deaths due to Road Traffic Injuries in Prehospital Phase; a Qualitative Study - Eftekhari, Adel; DehghaniTafti, Abbasali; Nasiriani, Khadijeh; Hajimaghsoudi, Majid; Fallahzadeh, Hossein; Khorasani-Zavareh, Davoud (Archives of Academic Emergency Medicine, 2019)
Introduction: Prehospital care plays an important role in decreasing the number of deaths due to road traffic injuries (RTIs). This study aimed to identify the challenges of preventable deaths due to RTIs in the prehospital phase based on the attitudes of stakeholders. Methods: Conventional content analysis of qualitative study was used to analyze the data. The participants were 24 RTI prevention experts from fire-fighting organization, traffic police, the Red Crescent, Emergency Medical Services staff, emergency medicine specialists, and hospital emergency nurses who were selected by means of purposive sampling. Data were collected using unstructured interviews and analyzed by means of data coding, followed by extracting sub-categories, and main categories. Results: Six main categories were extracted as the major challenges of preventable deaths in RTIs in the prehospital phase including â€œpoor management of the crash sceneâ€ with two subcategories of lack of rapid access to the patient and lack of scene safety, â€œlack of adequate rules and regulationsâ€ with two subcategories of lack of protocols and guidelines and lack of clear duties checklists, â€œpoor management of timeâ€ with two subcategories of elongated response time at the crash scene and elongated time of victim transport, â€œlow quality of trainingâ€ with two subcategories of insufficient training of Emergency Medical Services (EMS) staff and inadequate public training, â€œpoor communication and coordinationâ€ with two subcategories of poor communication of EMS staff and lack of uniform commandership at the crash scene, and â€œlow quality of victim managementâ€ with two subcategories of low quality of clinical care and lack of accurate clinical assessment. Conclusion: The following measures are necessary to reduce preventable deaths due to RTIs in the prehospital phase: accurate clinical assessment of the victim on the scene, provision of high quality and accurate clinical care, enforcement of legal obligations and using protocols in the field of victim management, coordination of the involved organizations through identifying the duties and responsibilities of each organization, and full management of the crash scene by assigning a unique commander to each unit and creation of the highest level of safety on crash scene.